1992
DOI: 10.1128/aac.36.2.435
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activities of ribavirin, 5-ethynyl-1-beta-D-ribofuranosylimidazole-4-carboxamide, and 6'-(R)-6'-C-methylneplanocin A against several ortho- and paramyxoviruses

Abstract: 5-Ethynyl-l-o-D-ribofuranosylimidazole-4-carboxamide (EICAR) and 6'-(R)-6'-C-methylneplanocin A (TJ13025) are two novel antiviral agents which are targeted against IMP dehydrogenase and S-adenosylhomocysteine hydrolase, respectively. These compounds have been examined for their activities against various strains of orthomyxoviruses (influenza virus) and paramyxoviruses (parainfluenza virus, mumps virus, measles virus, and respiratory syncytial virus) in vitro. EICAR was 10-to 59-fold more active than ribavirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0
2

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(71 citation statements)
references
References 18 publications
4
65
0
2
Order By: Relevance
“…Using the LDH method, ribavirin and EICAR showed lower values of the EC50 against FLUV-A, C, PFLUV and MPSV than those obtained by the PR method with monolayers of Vero, LLC-MK2, HeLa and MDCK cells (Shigeta et al 1992a). The EC50 values of ribavirin and EICAR by the LDH method were lower than those derived with the MTT method and in case of FLUV-C, PFLUV-1 and 3, the EC50 values were not obtained by the MTT method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the LDH method, ribavirin and EICAR showed lower values of the EC50 against FLUV-A, C, PFLUV and MPSV than those obtained by the PR method with monolayers of Vero, LLC-MK2, HeLa and MDCK cells (Shigeta et al 1992a). The EC50 values of ribavirin and EICAR by the LDH method were lower than those derived with the MTT method and in case of FLUV-C, PFLUV-1 and 3, the EC50 values were not obtained by the MTT method.…”
Section: Discussionmentioning
confidence: 99%
“…For anti-viral activity and cytotoxicity by MTT and PR methods, we followed methods described previously (Pauwels et al 1988;Takeuchi et al 1991;Shigeta et al 1992a). …”
Section: Determination Of Anti-viral Activity and Cytotoxicitymentioning
confidence: 99%
“…Ribavirin has proven to be an inhibitor of several ortho-and paramyxoviruses (42). Furthermore, ribavirin inhibits in vitro and in vivo replication of influenza virus (15,33,49,50), the most typical member of the Orthomyxoviridae family.…”
mentioning
confidence: 99%
“…The mortality among patients with MDRTB has ranged from 72% to 89%, and the median interval between the diagnosis of MDRTB and death has been short, ranging from 4 to 6 weeks [3].…”
mentioning
confidence: 99%
“…The case of patient 2 demonstrates that severe measles pneumonitis in immunocompetent adults, even when intubation and mechanical ventilation are required, can have a favorable course in the absence of specific therapeutic measures. Despite some evidence for an effect ofribavarin in patients with measles [3,4], the drug's value in adults has yet to be convincingly demonstrated. Porter et al noted that <30 cases of tuberculous bronchoesophageal fistulae (BEF) have been reported in the literature, and they described three additional patients who were infected with HIV [2].…”
mentioning
confidence: 99%